Immune checkpoint inhibitors in advanced and recurrent/metastatic cervical cancer - Han, Xiling; Chang, Wei-wei; Xia, Xiaoping (Frontiers in Oncology, 2022)
Cervical cancer (CC) poses a serious threat to women’s health. Although many early-stage patients have a good prognosis, there are still a lack of effective therapies for advanced and recurrent/metastatic CC. In this context, immunotherapy and immune checkpoint inhibitors (ICIs) are particularly likely to play a role in the treatment of cervical tumors in a variety of disease settings. Some promising immune checkpoints include programmed cell death 1 (PD-1), programmed death ligand 1 (PD-L1) and cytotoxic T lymphocyte antigen 4 (CTLA-4), which exert immunomodulatory effects as negative regulators of T-cell activation and suppress immune responses in cervical cancer through cancer cell immune evasion. Initial trials of ICIs for CC have shown encouraging results in terms of objective response rate (ORR), progression-free survival (PFS), and overall survival (OS), both monotherapy and combination strategies. Meanwhile, human papillomavirus, vaginal microecology and intestinal microenvironment play an important role in CC, which provides new treatment directions. This review analyzed a number of completed or ongoing clinical trials of ICIs in the treatment of advanced and recurrent/metastatic CC. And we also analyzed the important relationship between vaginal microecology and intestinal microecology with CC and their related immunotherapy prospects.